Incomplete Penetrance and Variable Expressivity: Hallmarks in Channelopathies Associated with Sudden Cardiac Death - Coll, Monica (Biology (Basel), 2017)
Sudden cardiac death is defined as an unexpected decease of cardiac origin. In individuals under 35 years old, most of these deaths are due to familial arrhythmogenic syndromes of genetic origin, also known as channelopathies. These familial cardiac syndromes commonly follow an autosomal dominant pattern of inheritance. Diagnosis, however, can be difficult, mainly due to incomplete penetrance and variable expressivity, which are hallmarks in these syndromes. The clinical manifestation of these diseases can range from asymptomatic to syncope but sudden death can sometimes be the first symptom of disease. Early identification of at-risk individuals is crucial to prevent a lethal episode. In this review, we will focus on the genetic basis of channelopathies and the effect of genetic and non-genetic modifiers on their phenotypes.